Association of sex and systemic therapy treatment outcomes in psoriasis: a two‐country, multicentre, prospective, noninterventional registry study. (22nd June 2021) - Maul, J.‐T.; Augustin, M.; Sorbe, C.; Conrad, C.; Anzengruber, F.; Mrowietz, U.; Reich, K.; French, L.E.; Radtke, M.; Häusermann, P.; Maul, L.V.; Boehncke, W.‐H.; et al.
Summary: Background: Few systematic data on sex‐related treatment responses exist for psoriasis. Objectives: To evaluate sex differences with respect to systemic antipsoriatic treatment. Methods: Data from patients with moderate‐to‐severe psoriasis in the PsoBest or Swiss Dermatology Network of Targeted Therapies (SDNTT) registries were analysed. Treatment response was defined as achieving a ≥ 75% reduction in Psoriasis Area and Severity Index (PASI 75) or PASI ≤ 3 at treatment months 3, 6 and 12, supplemented by patient‐reported outcomes [i.e. Dermatology Life Quality Index (DLQI) ≤ 1 and delta DLQI ≥ 4]. Results: In total, 5346 patients registered between 2007 and 2016 were included (PsoBest, n  = 4896; SDNTT, n  = 450). The majority received nonbiological treatment (67·3% male, 69·8% female). Women showed slightly higher PASI response rates after 3 (54·8% vs. 47·2%; P  ≤ 0·001), 6 (70·8% vs. 63·8%; P  ≤ 0·001) and 12 months (72·3% vs. 66·1%; P  ≤ 0·004). A significantly higher proportion of women achieved a reduction in DLQI ≥ 4 [month 3: 61·4% vs 54·8% ( P  ≤ 0·001); month 6: 69·6% vs. 62·4% ( P  ≤ 0·001); month 12: 70·7% vs. 64·4% ( P  ≤ 0·002)]. Regarding PASI ≤ 3, women on biologics showed a significantly superior treatment response compared with men at 3 (57·8% vs. 48·5%; P  ≤ 0·004) and 6 months (69·2% vs. 60·9%; P  ≤ 0·018). Women in the nonbiological treatment group had a significantly better treatment response (PASI response, PASI 75 and PASI ≤ 3) over 12 months compared with men. Conclusions: We provide evidence that women experience better treatment outcomes with systemic antipsoriatic therapy than men. Abstract : What is already known about this topic? Psoriasis is a stigmatizing disease that often affects females more negatively than males. Women show a higher burden of disease in psoriasis. It is largely unknown whether there are differences in response to systemic treatment according to sex. What does this study add? Women demonstrated a significant higher overall response than men for the totality of drugs studied. Women showed a significantly higher Psoriasis Area and Severity Index and Dermatology Life Quality Index response than men. Linked Comment:  P. Wolf. Br J Dermatol 2021; 185 :1088–1089 . Plain language summary available online